2012
DOI: 10.1177/0009922812468207
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in an Adolescent and Young Adult Gynecology Population

Abstract: Gynecologists see large numbers of patients exposed to bullying. Patients exposed in combinations of bully, victim, and witness have increased frequency of pelvic pain, depression, and anxiety. Patients do not disclose exposure to bullying to health care providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…6,67,75,114 Genital mutilation has also been correlated with dysmenorrhea, 44,45,83,127 although not consistently. 5,12,97 Small-scale studies of childhood immigration, 41 bullying, 124 and parental separation or death 152 have found no relationship with dysmenorrhea. Several factors may be contributing to inconsistencies observed between ACEs and dysmenorrhea including age at the time of trauma and whether it occurred premenarche or postmenarche.…”
Section: Social Influencesmentioning
confidence: 99%
“…6,67,75,114 Genital mutilation has also been correlated with dysmenorrhea, 44,45,83,127 although not consistently. 5,12,97 Small-scale studies of childhood immigration, 41 bullying, 124 and parental separation or death 152 have found no relationship with dysmenorrhea. Several factors may be contributing to inconsistencies observed between ACEs and dysmenorrhea including age at the time of trauma and whether it occurred premenarche or postmenarche.…”
Section: Social Influencesmentioning
confidence: 99%
“…However, the prevalence of voiding difficulties amongst victims of sexual abuse has been poorly explored and Williams et al have reported a case of episodic urinary retention in a woman who experienced recurrent sexual trauma. Other pelvic symptoms reported by individuals who have experienced abuse include pelvic pain, dyspareunia, and symptoms of prolapse …”
Section: Resultsmentioning
confidence: 99%
“…With regard to bullying and victimization former studies has validated links between mental health such as poor psychological well-being (Cook et al, 2010;Frieden, Sosin, Spivak, Delisle, & Esquith, 2012;Houbre et al, 2006), anxiety (eg: Boyle, 2005;Dake et al, 2003;Frieden et al, 2012;Houbre et al, 2006;McWhirter et al, 2013;Swearer et al, 2009) and depression (Kaltiala-Heino et al, 2010;Seltzer & Long, 2012;Zou et al, 2013). More recent studies suggest that vulnerabilities such as neurological and physiological , cognitive processing (Sarafino & Smith, 2014) and fear of peer rejection (Rodkin et al, 2015) may play vital role in being a bully or a victim.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%